Post-infection sequelae by COVID 19 in patients at Hospital I Florencia de Mora. Trujillo, Peru.: Secuelas post infección por COVID 19 en pacientes del Hospital I Florencia de Mora. Trujillo - Perú - Goicochea Ríos, Evelyn del Socorro (2022)
Objectives: To identify post COVID-19 sequelae in patients with medical discharge for this pathology. Methods: A prospective descriptive study was conducted between the second and fourth quarter of 2021 with a population of 330 patients diagnosed with COVID-19. Baseline was established at the beginning of the study, followed by follow-up and control consultation to identify post-COVID-19 sequelae and to perform control spirometry. Results: The frequency of COVID-19 was 29.78% (330 cases/1108 attended). The 43.94% of positive cases were in the 40-59 years age group, 28.8% (95/330) referred as comorbidity: cardiovascular disease, diabetes mellitus II and bronchial asthma. Post COVID-19 sequelae predominated: respiratory (61%), musculoskeletal (43%) and neurological (20%), with dyspnea, dorsalgia and headache, respectively. The duration of sequelae ranged from 21 days to seven months, spirometry showed a mild restrictive pattern in patients aged 41 to 50 years, all female. Conclusions: It is important to identify post-COVID-19 sequelae for treatment to recover the integral health of individuals.